Workshop Pengolahan dan Penerbitan Jurnal Keperawatan Terakreditasi bagi Dosen - Fadhilah, Umu; Liestyaningrum, Wiwiek; Pujiati , Wasis; Sina, Cian Ibnu; Lizawati, Lizawati; Khaulani, Dzarin Gifarian (SEGANTANG LADA : JURNAL PENGABDIAN KESEHATAN, 2024)
Scientific journals are one of the important indicators for scientific development to facilitate the scientific work of students and lecturers. Every university is obliged to have a journal. The scientific work of students and lecturers is required, and every university must have a scientific journal based on the Open Journal System (OJS) that must be accredited nationally and internationally. Scientific journals based on the Open Journal System must be nationally and internationally accredited. Stikes Hang Tuah Tanjungpinang already has one nursing journal. However, it has not yet been professionally managed regarding article management, review process, and copy editing, so the accreditation requirements have not been met. This training aims to provide explanations and workshops on managing scientific journals so that they can be accredited nationally. This community service activity was carried out in March 2023 for 3 days. This training was attended by approximately 27 participants from Lecturers and Staff who were located in the Stikes Hang Tuah Tanjung Hall Room. Service activities are carried out in 3 stages: 1) OJS Installation Process by the PKM Team with the Partner Team, and Pre-tests to determine the participants' knowledge of journal management with OJS. Journal management with OJS. 2) training through lectures and discussions and direct assistance conducted offline. 3) Evaluation After conducting online journal management training with OJS, the post-test results show an increase in percentage up to 100% for knowledge questions about the Open Journal System (OJS) website. This training is successful and right on target. Suggestions are expected journal training like this can be carried out on an ongoing basis so that journals can develop better.